Orbital and physical parameters of eclipsing binaries from the ASAS catalogue – XI. CHIRON investigation of long-period binaries. Issue 4 (10th November 2020) - Ratajczak, M; Pawłaszek, R K; Hełminiak, K G; Konacki, M; Sybilski, P; Kozłowski, S K; Litwicki, M; Smith, A M S; Mikołajczyk, P; Anderson, D R; Hellier, C
ABSTRACT: We present the results of a spectroscopic campaign on eclipsing binaries with long orbital period ( P = 20–75 d) carried out with the CHIRON spectrograph. Physical and orbital solutions for seven systems were derived from the V band, and I band ASAS, WASP, and TESS photometry, while radial velocities were calculated from high-quality optical spectra using a two-dimensional cross-correlation technique. The atmospheric parameters of the stars have been determined from the separated spectra. Most of our targets are composed of evolved stars (subgiants or red giants) but two systems show components in different phases of evolution and one possible merger. For four binaries, the masses and radii of the components were obtained with precision better than 3 per cent . These objects provide very valuable information on stellar evolution.